Innovative green building forms for sustainable community - Tay, Kwang Hong. (2011)
The aim of the final year project is to increase the wind speed flowing through an industrial park by building linkages between buildings so as to reduce the pollutant concentration. The building of linkages will allow the buildings in the Industrial Park to be build taller but shorter in length.. This report employs a Gaussian area source model to quantify the relationship between the wind speed and the pollutant concentration in a box model. It has been determined that wind speed has an effect on pollutant concentration where higher wind speed will result in a lower pollutant concentration. Square shaped buildings is deemed better than circle shaped building after comparing the area of dead zone in a specific area. Lastly, increasing the width and height of buildings to a certain extend will result in a less area of dead zone as it will give a higher wind speed which in turn will reduce the overall air pollutant concentration. The proposed design with a similar usable floor but lesser foot print as the Bukit Batok Industrial Park is able to give a higher wind speed.